Screening of Antioxidant and Antibacterial Activities of Mulberry - Thipamon Patharakorn; Nuanchawee Wetprasit; Amornrat Promboon; Sunanta Ratanapo (Agriculture and Natural Resources, 2006)
Hot-water and methanolic extracts from tea-leaves and roots of various silkworm-mulberry cultivars (Morus spp.) were investigated for their phenol contents, antibacterial and antioxidative activities. Phenol contents obtained by methanolic extraction were higher than the hot-water extraction and differed between cultivars and parts of the plant. Radical scavenging activity of each mulberry extract was measured spectrophotometrically using a stable radical, ABTS +• [2,2’-azino-bis(3-ethylbenzthiazoline- 6-sulfonic acid)] in comparison to quercetin while antioxidant power was evaluated as efficient concentration, EC50. Most mulberry cultivars exhibited the highest antioxidant efficiency in roots and lower in fruits and leaves, respectively. EC50 of hot-water extracts of mulberry tea-leaves lied between 0.19 to 0.70 in which China44 showed the highest antioxidant activity with EC50 of 0.19 with phenol content of 6.17 mg/g dry wt. EC50 of hot-water extracts of mulberry roots lied between 0.11 to 0.70 in which Mon-Noi showed the highest antioxidant activity with EC50 of 0.11 with phenol content of 5.89 mg/g dry wt. EC50 of methanolic extracts of mulberry roots lied between 0.08 to 0.24 in which Khun-Pi showed the highest antioxidant activity with EC50 of 0.08 and with phenol content of 7.28 mg/g dry wt. Methanolic extracts of the fruits gave nearly equal EC50, lied between 0.30 to 0.39, a little higher than that of hot-water extracts. Antibacterial activities of hot-water extracts of mulberry tea-leaves and methanolic extracts of the roots were evaluated by agar diffusion method. The differences in antibacterial potencies were revealed among mulberry cultivars and parts of the plant. It was found that six of fortyone human-pathogenic bacterial strains were inhibited by the tea-leaf extracts whereas twelve strains were inhibited by the root extracts.